2016
DOI: 10.1080/13803395.2016.1227427
|View full text |Cite
|
Sign up to set email alerts
|

Exercise during pregnancy enhances cerebral maturation in the newborn: A randomized controlled trial

Abstract: Accumulating research indicates that the regular practice of physical exercise is beneficial to the human brain. From the improvement of academic achievement in children to the prevention of Alzheimer's disease in the elderly, exercise appears beneficial across the developmental spectrum. Recent work from animal studies also indicates that a pregnant mother can transfer the benefits of exercise during gestation to her offspring's brain. Exercising pregnant rats give birth to pups that have better memory and sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 27 publications
0
56
1
Order By: Relevance
“…Jukic et al is the only study reporting possible poor outcome of general physical activity in pregnancy but this was an unexpected finding questioned by the authors. Neither the results from the present or previous RCTs nor the observational studies suggest poor neurodevelopmental outcomes for children whose mothers were physically active or exercised during pregnancy. Hence, there is good reason to assume that exercise during pregnancy is not harmful for the child’s neurodevelopment.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Jukic et al is the only study reporting possible poor outcome of general physical activity in pregnancy but this was an unexpected finding questioned by the authors. Neither the results from the present or previous RCTs nor the observational studies suggest poor neurodevelopmental outcomes for children whose mothers were physically active or exercised during pregnancy. Hence, there is good reason to assume that exercise during pregnancy is not harmful for the child’s neurodevelopment.…”
Section: Discussioncontrasting
confidence: 90%
“…Two RCTs have examined the effect of exercise on children’s neurodevelopment . No adverse effects on brain responses in infancy or differences in the children’s cognitive, language and motor skills at 18 months of age were found .…”
Section: Introductionmentioning
confidence: 99%
“…The total sample included in the randomised controlled trials was 277 children (122 in sedentary groups). Cohorts were from Canada and Norway . The mothers’ age at birth ranged from 27 to 30.5 years, and children's neurocognitive development was assessed when they were 10 days old and 20 months old.…”
Section: Characteristics Of Observational and Randomised Controlled Tmentioning
confidence: 99%
“…Previous studies have reported that physical exercise programmes during pregnancy are associated with children's higher scores in orientation, state regulation, academic achievement and cognition . Different pathways behind this relation have been proposed including improvements in the intrauterine environment, better circulation and higher placental volumes, and a decreased risk of gestational depression, a disorder that is known to have a negative effect on the psychological development in early infancy …”
Section: Introductionmentioning
confidence: 99%
“…Taken together with the developmental origins of health and disease (DOHaD) paradigm (Gluckman et al, 2010), the importance of lifestyle factors (e.g., smoking, alcohol, drugs, caffeine, weight and others), vaccinations, chronic diseases and environmental exposures to the fetus CNS development have been highlighted during this period (Dean et al, 2014). Interestingly, literature is scarce concerning lifestyle interventions during pregnancy, despite the growing evidence that healthy lifestyle is associated with improved pregnancy outcomes for both mothers and offspring (Labonte‐Lemoyne et al, 2017).…”
Section: Introductionmentioning
confidence: 99%